Endoleaks after endovascular abdominal aortic aneurysm repair - Kramek, Jakub Tomasz; Stępak, Hubert; Oszkinis, Grzegorz (Journal of Medical Science, 2017)
Traditional surgical repair and endovascular repair (EVAR) are the treatment options for abdominal aortic aneurysm repair. EVAR as less invasive becomes a significant and widely accepted way of treatment aortic aneurysms with expanding number of procedures. This technique has a lover short-term mortality and a shorter hospital stay but is not free from complications. The most common complication after EVAR are endoleaks. For the first time summarised and assessed in 1997. Although it is often asymptomatic but may cause aneurysm expanding and rupture. Endoleak is defined as persistent blood flow into the aneurysm sac. It can be revealed intra-operatively or during the follow up – CT; arteriography, angio-MRI enables endoleak diagnosis. Usage of duplex sonography is questionable. In this mini-review we summarise endolek diagnostic, classification and treatment options.